Mozambique Economic Update, February 2021 : Setting the Stage for Recovery - World Bank (Washington, DC: World Bank, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better'.